THE COINAGE OF AL-ANDALUS - Almudena ARIZA ARMADA (Fayoum University, 2017)
This paper presents the evolution of Andalusi coins, from the first issues that appeared during the Islamic conquest of the Iberian Peninsula, continuing with the Umayyad issues of Al-Andalus (Emirate and Caliphate), the Ḥammūdid ones and those of 11th century Ṭāۥ ifas’ as well as the ones issued by Almoravid and Almohad dynasties, until the last ones, struck under the Naṣriddynasty of Granada. A comprehensive view on the evolution of these coins is offered from a new perspective, including the latest contributions to the knowledge we have on this subject and raising new hypotheses. This paper is an update in which the main characteristics of the Andalusi coins of each period framed in its historical context are explored: coin legends, epigraphical characteristics, metrology, etc.; elements that turn the coins into a symbol of power of the different political authorities that ruled Al-Andalus.